2016
DOI: 10.1111/1440-1630.12298
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy in Australian acute hospitals: A modified practice

Abstract: Western Australian acute care occupational therapists are practising in a highly complex health context that presents many challenges. They are responding by using a modified form of practice that ensures occupational therapy skills remain relevant within the narrow confines of this health setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…Systemic barriers such as the focus on medical management as a priority, and the discharge-focused nature of traditional healthcare, could affect uptake of even the most basic of changes to practice or interventions (Novak and McIntyre, 2010). Furthermore, Britton et al (2016) and Wilding and Whiteford (2009) described time constraints and the difficulty of deviating from accepted standards of practice as other challenges. It was evident from the interviews that these were common barriers for new and recent graduates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic barriers such as the focus on medical management as a priority, and the discharge-focused nature of traditional healthcare, could affect uptake of even the most basic of changes to practice or interventions (Novak and McIntyre, 2010). Furthermore, Britton et al (2016) and Wilding and Whiteford (2009) described time constraints and the difficulty of deviating from accepted standards of practice as other challenges. It was evident from the interviews that these were common barriers for new and recent graduates.…”
Section: Discussionmentioning
confidence: 99%
“…Some occupational therapy research has recently focused on the implementation of occupational approaches in acute hospital settings (Britton et al., 2016; Di Tommaso et al., 2016; Wilding and Whiteford, 2008). In particular, Wilding and Whiteford’s action research study in an Australian hospital found that when occupational therapists more explicitly included occupation in their practice they experienced increased confidence, professional connection and motivation to achieve occupation-based practice (Wilding and Whiteford, 2008, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When occupational therapists are pushed by the biomedical model to use a human deficit discourse and other language such as 'function', they may contribute to the public's confusion about the occupational therapy profession (Di Tommaso & Wilding, 2014;Prodinger, Shaw, Rudman & Townsend, 2012;Wilding & Whiteford, 2008). Occupational therapists may benefit from critical reflection facilitated through supervision, which may provide a platform for them to articulate and consider ways to make their practice more occupation-focussed (Britton, Rosenwax & McNamara, 2016).…”
Section: The Implications Of a Tacit Occupational Perspectivementioning
confidence: 99%
“…Those participants adjusted the constructive concepts by reflecting on the chronological and physical realities and the payment system for medical services. In a similar way, according to Britton, Rosenwax, and McNamara (2016), occupational therapists who worked in an Australian hospital described difficulties constructing their professional identities in an acute care setting. The participants modified their practices using the following three strategies: becoming the client advocate, being the facilitator, and applying clinical reasoning.…”
Section: States Thatmentioning
confidence: 94%